2013
DOI: 10.1186/1479-5876-11-110
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the vasculature supporting growth of primary patient tumor xenografts

Abstract: BackgroundStudies of primary patient tumor xenografts grown in immunodeficient mice have shown that these tumors histologically and genetically closely resemble the original tumors. These patient xenograft models are becoming widely used for therapeutic efficacy studies. Because many therapies are directed at tumor stromal components and because the tumor microenvironment also is known to influence the response of a tumor to therapy, it is important to understand the nature of the stroma and, in particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…However, to avoid immune rejection of xenotransplants by the host, PDX models are primarily generated by transplanting tumour fragments into immunodeficient mice. The absence of 15 many components of the immune system in these mice, and the loss of endogenous human immune cells upon propagation of the human tumour tissue over multiple passages 70,71 , limit the utility of such models to explore the role of the immune system in tumour progression and to test novel immune-based therapies 72 .…”
Section: Next-generation Pdx Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to avoid immune rejection of xenotransplants by the host, PDX models are primarily generated by transplanting tumour fragments into immunodeficient mice. The absence of 15 many components of the immune system in these mice, and the loss of endogenous human immune cells upon propagation of the human tumour tissue over multiple passages 70,71 , limit the utility of such models to explore the role of the immune system in tumour progression and to test novel immune-based therapies 72 .…”
Section: Next-generation Pdx Modelsmentioning
confidence: 99%
“…However, to avoid immune rejection of xenotransplants by the host, PDX models are primarily generated by transplanting tumour fragments into immunodeficient mice. The absence of many components of the immune system in these mice, and the loss of endogenous human immune cells upon propagation of the human tumour tissue over multiple passages 70,71 , limit the utility of such models to explore the role of the immune system in tumour progression and to test novel immune-based therapies 72 Although these procedures are known to cause severe graft-versus-host disease (GvHD) beginning 2-5 weeks after injection 73,74 , seriously limiting the useful investigative time window of these models and the translational value of these studies 75 , PBL and TIL mice can be used for cost-effective short-term testing of novel immune therapeutics and for assessing short-term adverse effects.…”
Section: Next-generation Pdx Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the limitations of PDXas are the serial passaging of the tumors, which can be lengthy and cause loss of clonal diversity, and replacement of human stroma and human vasculature (27,28). Methods that establish primary cell lines and PDXas in parallel allow for faster in vivo and in vitro testing that could direct therapeutic strategies for individual patients in real time (19,(29)(30)(31)(32), making ascites an ideal source of material for xenografts, which we distinguished from biopsy PDXs by referring to them as PDXas.…”
Section: Discussionmentioning
confidence: 99%
“…Direct analysis addressing the fate of stromal components of the original graft or stromal changes upon propagation are still warranted today (28). However, recent studies by Hylander et al demonstrated that the human microvasculature of a colon PDX is partially replaced by host vessels as early as three weeks (33). Additionally, Lin et al reported that more than 40% of analyzed pancreatic PDXs harbored less human than mouse DNA, supporting the presence of infiltrating murine cells (34).…”
Section: Finding the Perfect Castmentioning
confidence: 99%